Data related to "Emissions of atmospherically reactive gases nitrous acid and nitric oxide from arctic permafrost peatlands" - Bhattarai, Hem Raj; Marushchak, Maija E.; Ronkainen, Jussi; Lamprecht, Richard E.; Siljanen, Henri M.P.; Martikainen, Pertti J.; Biasi, Christina; Maljanen, Marja (Zenodo, 2022)
The data file contains the individual (each replicate) values of the soil variables and gas fluxes obtained from the study. It contains data shown in the both main text and supplementary files.